The galaninergic enteric nervous system of pleuronectiformes (Pisces, Osteichthyes) : an immunohistochemical and confocal laser scanning immunofluorescence study - G. Bosi; C. Domeneghini; R. Bermudez (General and Comparative Endocrinology, 2007)
The galaninergic enteric nervous system of three flatfishes was studied using immunohistochemical and immuno fluorescence methods. Galanin-like immunoreactivity was mainly detected within the enteric intramural neurons of the stomachs and the proximal intestines. The sole, Solea solea L. and the flounder, Platichthys flesus L. showed a similar occurrence and relative distribution of galaninergic intramural neurons. Rare nervous fibre immunoreactive to the anti-galanin serum were observed in the muscular layers of the oesophagus of the turbot, Psetta maxima L. The presence and relative abundance of galanin-like immunoreactive neurons in the remaining organs of the alimentary canal of the turbot showed a different pattern in comparison to those observed in the sole and the flounder. A galanin-like peptide was detected in nerve fibres running through the exocrine parenchyma of the pancreas of all three species. It is conceivable that the galaninergic system in these species plays a role in regulating gut muscle activity, and in controlling pancreatic secretion. Galanin and choline acetyltransferase were co-localized within the same neurons of the stomach and intestine. The result confirms the hypothesis that galanin in the gut of fish functions as a cholinergic modulator. Differently from other fish species, immunoreactive endocrine cells were not detected in the studied pleuronectiformes